Pengaruh Media Interaktif terhadap Peningkatan Keterampilan Membaca Puisi Siswa Kelas X - Taqdiraa; Halimatusya'diyah; Kalukar, Ventje; Susilo; Azainil (Jurnal Tinta, 2025)
This study aims to determine the effect of the use of interactive media on improving poetry reading skills of class X students. This study is based on the low ability of students to understand the meaning of poetry in depth which is characterized by weak mastery of diction, intonation, and appreciation. This study uses a quantitative approach with a quasi-experimental design type Pretest-Posttest Nonequivalent Groups Design. The research sample consisted of two classes, each consisting of 27 students, namely the experimental group using interactive media in the form of poetry musicalization learning videos, and the control group using conventional methods. The research instrument was a multiple-choice test accessed through Google Form. The results of data analysis showed that the average posttest score of students in the experimental group (78.5) was significantly higher than that of the control group (68.4), with a significance value (Sig. 2-tailed) = 0.000 <0.05. Thus, it can be concluded that the use of interactive media has a significant effect on improving students' poetry reading skills.